Training to Improve Customer Satisfaction by Developing Discount Pricing - Marliyah, Marliyah; Alifatuzzahra, Nisa; Rahmah, Mutiara (Taqaddum: Community Service Journal, 2023)
In the business world, many companies offer similar goods or services, leading to intense competition. To stand out, companies must employ innovative strategies and effective promotions to attract customers. One common promotional strategy is offering discounts, which involves reducing the price of goods to make them more appealing to consumers. Discounts serve as a tool to increase consumer interest in purchasing a product within a specified time frame. Customer satisfaction, in this context, refers to the extent to which a customer's expectations and needs are met, particularly regarding the perceived value of the purchase. This study explores the effect of price cuts through discounts on customer satisfaction. The research was conducted using a situational approach, analyzing real-time customer responses and feedback during promotional periods in selected retail stores. Data was collected through direct observation and surveys, providing insights into consumer behavior and satisfaction levels related to discounted products.